MASS-TRANSPORT TO CHANNEL AND TUBULAR ELECTRODES - THE SINGH AND DUTT APPROXIMATION - Compton, R; Pilkington, M; Stearn, G; Unwin, P (1987)
A potentially extremely useful simplifying approximation introduced by Singh and Dutt (J. Electroanal. Chem., 182 (1985) 259) for the mathematical treatment of mass transport in channel and tubular electrodes is examined in the light of more rigorous theory. The approximation involves the modification of the convective-diffusion equation by replacing concentration gradients in the direction of flow by their average values. This then facilitates the ready solution of the equation by straightforward analytical methods. Although the approximation is shown, at first sight, to lack an obvious physical basis, it is found to be remarkably successful when applied to a range of problems including both time-dependent phenomena (such as chronoamperometry) and also complex steady-state problems (such as the current-flow rate behaviour of ECE and DISP1 processes). The success of the approximation can be judged from the observation that the consequences of subtle changes in mechanism, e.g. from ECE to DISP1, can be predicted accurately. A rationalisation of the approximation is presented. It is anticipated that the widespread adoption of the approximation should greatly ease the application of channel electrodes in a diversity of problems for which theory has hitherto been lacking. © 1987.